2016
DOI: 10.1177/1940161216631114
|View full text |Cite
|
Sign up to set email alerts
|

Protesting the Paradigm

Abstract: This study assesses the scope and applicability of the "protest paradigm" in non-Western contexts by examining the news coverage of Brazilian, Chinese, and Indian protests in their domestic media. Two publications from each nation, one conservative and one progressive, are content analyzed for adherence to a series of marginalization devices that have often been used by the U.S. media to ridicule protest movements and portray them as violent. The Indian media emerge as the least likely to follow the protest pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 52 publications
1
23
0
2
Order By: Relevance
“…Wittebols (1996) showed that news coverage of protests was more favorable when protesters' issues aligned with the government's foreign policies. Other studies suggest that general attitudes toward protest activity can influence adherence to the paradigm, as the more protesters are seen as outsiders, the more negative coverage will be (Shahin et al 2016;Streeck and Kenworthy 2005). Kim and Shahin (2019) pointed out that news media ideological similarities could sometimes overcome national boundaries when covering certain social movements and protests.…”
Section: Protest Issue and Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wittebols (1996) showed that news coverage of protests was more favorable when protesters' issues aligned with the government's foreign policies. Other studies suggest that general attitudes toward protest activity can influence adherence to the paradigm, as the more protesters are seen as outsiders, the more negative coverage will be (Shahin et al 2016;Streeck and Kenworthy 2005). Kim and Shahin (2019) pointed out that news media ideological similarities could sometimes overcome national boundaries when covering certain social movements and protests.…”
Section: Protest Issue and Locationmentioning
confidence: 99%
“…While previous studies have identified various factors that limit adherence to the paradigm (e.g., Cottle, 2008;Harlow and Johnson 2011;Shahin et al 2016), little research has attempted to comprehensively show how the paradigm in stories shared on social media varies across the world in different types of media. With this in mind, we offer a typology to better explain how the protest paradigm operates across countries, languages, protest topic, and types of media outlets in this social media age (see Figure 1).…”
Section: Typologymentioning
confidence: 99%
“…Later studies have often reused these frames but measured how commonly they appeared through quantitative content analysis. This enabled researchers to compare how commonly frames linked to the protest paradigm are used in different countries (e.g., Dardis, 2006, Shahin et al (2016); Harlow et al, 2020), for different kinds of protests (e.g., Kilgo and Harlow, 2019; De Cillia and McCurdy, 2020), employing different tactics (e.g., Wouters, 2015; Wasow, 2020) between different news outlets (e.g., Kyriakidou and Olivas Osuna, 2017; Kim and Shahin, 2020), on social media sites (e.g., Mourão et al, 2021; Harlow and Johnson, 2011; Harlow et al, 2020), and over time (e.g., Gil-Lopez, 2020; Jha, 2007). However, while some studies have complemented the original set with inductively identified frames (e.g., Kyriakidou and Olivas Osuna, 2017; Mourão et al, 2021), Kleut and Milojevic (2021) remark that the original set by McLeod and Hertog (1999) has rarely been assessed for completeness by fully inductive research strategies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Existing scholarship on media coverage of BLM focuses exclusively on the US context and was not designed to analyze coverage outside of the United States. While protest paradigm approaches have been applied in comparative examinations of the American and foreign media (Di Cicco 2010; Harlow and Johnson 2011; Shahin et al 2016), research has also highlighted variations in the applicability of the paradigm depending on factors such as protesters’ tactics, journalists’ own preferences, or the perceived legitimacy of informal power negotiations (Boyle et al 2012; Shahin et al 2016; Tenenboim-Weinblatt 2014).…”
Section: Framework For Understanding Coverage Of Blmmentioning
confidence: 99%